A CO2-induced ROCO2Na/ROCO2H buffer solution promoted the carboxylative cyclization of propargyl alcohol to synthesize cyclic carbonates. Issue 3 (3rd January 2020) - Yan, Shaorui; Zhou, Ruinian; Han, Feng; Feng, Mengmeng; Miao, Chengxia; Zhang, Shuai; Ai, Shiyun
Abstract : A CO2 -induced ROCO2 Na/ROCO2 H buffer solution is developed and employed in the carboxylative cyclization of propargyl alcohol to generate α-alkylene cyclic carbonates. Abstract : A CO2 -induced ROCO2 Na/ROCO2 H buffer solution is developed and employed in the carboxylative cyclization of propargyl alcohol to generate α-alkylene cyclic carbonates. The introduction of CO2 into the propargyl alcohol/sodium tertiary pentoxide system can provide the ROCO2 Na/ROCO2 H buffer solution with both basic and acidic species. The basic and acidic species can simultaneously promote the generation of a carbonate anion intermediate and the interaction between the alkyne moieties of propargyl alcohol and protons (H + ), facilitating carboxylative cyclization. Furthermore, the bulky ( n -C4 H9 )4 N + cation of tetrabutylammonium bromide as an additive plays a crucial role in enhancing the nucleophilicity of the carbonate anion intermediate. Various α-alkylene cyclic carbonates are obtained in this catalytic system with relatively good yields at 80 °C.